Contribution of Social Disclosure and Organizational Culture to Create Financial Value of Tunisian Companies - Rahma, Driss; Anis, Jarboui (Growth, 2015)
The main objective of this paper is to explain the contribution of the social disclosure and the characteristics of organizational culture on the level of financial value creation of Tunisian companies. Theoretically, we supported a literature review rich in theoretical and empirical studies of relationship between these concepts. This theoretical framework allowed us to develop our research hypotheses. As for methodology, we worked on a sample of 23 Tunisian companies listed in Tunis Stock Exchange on a five-year period extending from 2007 to 2011.Finally for the results, we found, first, that the social disclosure has a remarkable effect on creating financial value. On the other hand, we find that organizational culture has a significant influence on creating financial value of companies through some items, namely: collaboration skills and organizational learning.